Inter- and intra-individual variation in urinary excretion of daidzein and equol in female Japanese. (August 2014) - Suzuki, Yayoi; Hisada, Aya; Yoshinaga, Jun
Abstract Objective: To evaluate the representativeness of single measurement of urinary soy-isoflavone concentrations for the assessment of long-term intake levels. Methods: Five urine samples taken from 14 Japanese female subjects over 2–3 months were measured for daidzein and equol by gas chromatography-mass spectrometry (GC-MS). Results: Geometric mean daidzein and equol concentrations of 14 subjects were 582 and 2.66 μg/g creatinine, respectively. Intra-class correlation coefficients for daidzein and equol were 0.355 (95% CI: 0.130–0.649) and 0.741 (0.551–0.891), respectively. Conclusion: Single measurement of urinary equol is effective for the assessment of long-term equol status of Japanese subject while that of daidzein is not.